Determination of the Dissolution/Permeation and Apparent Solubility for Microencapsulated Emamectin Benzoate Using In Vitro and Ex Vivo Salmo salar Intestine Membranes - Victoria Molina; Carlos von Plessing; Alex Romero; Sergio Benavides; José Miguel Troncoso; José Ricardo Pérez-Correa; Wendy Franco (Pharmaceuticals, 2022)
In this work, two microencapsulation techniques were used to protect and improve the absorption of emamectin benzoate (EB), which is an antiparasitic drug used to control Caligus rogercresseyi . EB has a low aqueous solubility, which affects its absorption in the intestine of Salmo salar . Microparticles were produced by spray drying and ionic gelation, using Soluplus ® (EB–SOL) and sodium alginate (EB–ALG) as polymers, respectively. Studies were conducted on dissolution/permeation, apparent permeability (Papp), apparent solubility (Sapp), and absorption using synthetic and biological membranes. Based on these results, the amount of EB in the microparticles needed to achieve a therapeutic dose was estimated. The EB–ALG microparticles outperformed both EB–SOL and free EB, for all parameters analyzed. The results show values of 0.45 mg/mL (80.2%) for dissolution/permeation, a Papp of 6.2 mg/mL in RS–L, an absorption of 7.3% in RS, and a Sapp of 53.1% in EM medium. The EB–ALG microparticles decrease the therapeutic dose necessary to control the parasite, with values of 3.0 −2 mg/mL and 1.1 −2 mg/mL for EB in EM and RS, respectively. The Korsmeyer–Peppas kinetic model was the best model to fit the EB–ALG and EB–SOL dissolution/permeation experiments. In addition, some of our experimental results using synthetic membranes are similar to those obtained with biological membranes, which suggests that, for some parameters, it is possible to replace biological membranes with synthetic membranes. The encapsulation of EB by ionic gelation shows it is a promising formulation to increase the absorption of the poorly soluble drug. In contrast, the spray-dried microparticles produced using Soluplus ® result in even less dissolution/permeation than free EB, so the technique cannot be used to improve the solubility of EB.